Simple indictor of increased blood culture contamination rate by detection of coagulase-negative staphylococci - Yamamoto, Kei; Mezaki, Kazuhisa; Ohmagari, Norio (Scientific Reports, 2021)
Coagulase-negative staphylococci (CoNS) are the most frequent contaminating bacteria; therefore, we aimed to investigate an indicator of CoNS to predict the increase in blood culture contamination rate (ConR). We performed a retrospective study of selected patients, who underwent blood culture testing. Contamination was defined as the presence of either one of two or more sets of skin-resident bacteria, except for cases with a low likelihood of contamination based on clinical aspects. We calculated the monthly ConR [(total number of contaminated cases per month)/(total number of blood culture sets collected per month) × 100] and analysed the ConR prediction ability using the following four indicators: the number of CoNS-positive sets of blood cultures, cases with at least one CoNS-positive blood culture set, cases with only one CoNS-positive blood culture set, and cases of contamination by CoNS. Cases with CoNS-positive blood cultures correlated with ConR (r = 0.85). Although the area under the receiver operating characteristic curve for the number of cases with ConR ≥ 2.5 differed significantly from that of the number of cases contaminated by CoNS, the negative predictive value was high, reaching up to 95.5% (95% confidential interval 87.3–99.1). The number of CoNS-positive cases could help predict an increase in ConR ≥ 2.5.